Waterproof oil-proof high-viscosity adhesive and preparation method thereof

By cation exchange with montmorillonite and co-constructing a three-dimensional network structure with vinyl triethoxysilane, the problem of decreasing bond strength of polyvinyl acetate emulsion in high humidity environments is solved, and high viscosity, waterproof and oil-resistant performance are improved.

CN119709028AActive Publication Date: 2025-03-28WUHAN HUACAI OPTOELECTRONICS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411751312.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-28
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing polyvinyl acetate emulsions are prone to absorb water in high humidity environments or in water, resulting in a decrease in bonding strength, poor water and oil resistance, low viscosity, and difficult to meet the application needs of many fields.

Method used

By cation exchange with montmorillonite through the modified polyacrylic emulsion, organic groups are covered or inserted between the montmorillonite layers, increasing the layer spacing, improving dispersion and stability, and jointly building a three-dimensional network structure with vinyl triethoxysilane to enhance the cohesion and viscosity of the adhesive, and at the same time, Si-O-Si bonds are introduced to improve waterproof and oil-resistant properties.

Benefits of technology

It significantly improves the waterproof and oil-proof performance and strength of the adhesive, enhances viscosity, and maintains the bonding strength in high humidity environments, meeting the application needs of many fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005165063260000061
    Figure BDA0005165063260000061
  • Figure BDA0005165063260000071
    Figure BDA0005165063260000071
Patent Text Reader

Abstract

The invention discloses a waterproof oil-proof high-viscosity adhesive and a preparation method thereof, and relates to the technical field of adhesives. According to the invention, cation exchange is carried out among montmorillonite layers through modified polyacrylic acid emulsion, the dispersibility and stability of montmorillonite are improved, the modified polyacrylic acid emulsion and vinyltriethoxysilane jointly participate in the construction of a three-dimensional network structure among polyvinyl acetate polymer molecules, the cohesion and tensile strength of the adhesive are enhanced, and Si-O-Si bonds are introduced, so that the adhesive has good mechanical properties. The waterproof and oil-proof performance and the strength of the adhesive are further improved. Wherein the modified polyacrylic acid emulsion is prepared by carrying out copolymerization on N-hexyl-N-methacryloyloxy-N, N-dimethylamino ammonium bromide, (1-allyl-1H-benzimidazole-2-yl) methanol and acrylic acid by virtue of an emulsion method; a long chain segment is introduced, so that water molecules are repelled outside the surface of the material, and the waterproof and oil-proof performance of the adhesive is enhanced; benzimidazole can form a layer of protective film on the bonding surface to prevent contact of media such as oxygen and moisture, so that waterproof and oil-proof effects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, in particular to a waterproof and oil-proof high-viscosity adhesive and a preparation method thereof. Background Art

[0002] Polyvinyl acetate (PVAc) emulsion, commonly known as "white latex", is widely used in many fields such as architectural coatings, wood bonding, paper processing, textile printing and dyeing, cement modification, glass fiber processing, and home decoration. Polyvinyl acetate emulsion has low cost and a relatively simple polymerization process. It is non-toxic, tasteless, odorless, colorless and transparent, and has good bonding, light resistance, and is not easy to age. As a water-based adhesive, it has great advantages over solvent-based adhesives in terms of greenness, energy saving, and environmental protection.

[0003] However, PVAc also has disadvantages such as poor water and oil resistance and low viscosity. PVAc emulsion film is easy to absorb water and the bonding strength drops sharply in a high humidity atmosphere or after being soaked in water. In order to make PVAc emulsion be used in different fields, people usually modify it, such as blending, copolymerization, cross-linking, protective colloid modification, etc. to meet the performance. Since the 1980s, domestic and foreign scholars have done a lot of research on the protective colloids and initiators used in PVAc emulsion polymerization, in order to prepare water-resistant polyvinyl acetate emulsion without affecting its coating, stability and other properties. Therefore, the development of a PAVc emulsion with good water and oil resistance has gradually become a trend. Summary of the invention

[0004] The object of the present invention is to provide a waterproof and oil-proof high-viscosity adhesive and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a waterproof and oil-proof high-viscosity adhesive, which comprises, by weight, 8 to 14 parts of a composite modified polyacrylic acid emulsion, 45 to 55 parts of vinyl acetate, 0.5 to 1.5 parts of ammonium persulfate, 0.1 to 0.3 parts of a preservative, 2 to 6 parts of a film-forming aid, and 44 to 62 parts of deionized water.

[0006] Furthermore, the composite modified polyacrylic acid emulsion is prepared by combining modified polyacrylic acid emulsion with montmorillonite and vinyltriethoxysilane.

[0007] Furthermore, the modified polyacrylic acid emulsion is prepared by copolymerizing N-hexyl-N-methacryloyloxy-N,N-dimethylaminoammonium bromide, (1-allyl-1H-benzimidazol-2-yl)methanol and acrylic acid through an emulsion method.

[0008] Furthermore, a method for preparing a waterproof and oil-proof high-viscosity adhesive comprises the following preparation steps:

[0009] (1) 2 to 6 parts of N-hexyl-N-methacryloyloxy-N,N-dimethylaminoammonium bromide, 5 to 9 parts of (1-allyl-1H-benzimidazol-2-yl) methanol, and 24 to 50 parts of acrylic acid are uniformly mixed to obtain a mixed solution, 1 / 3 of the mixed solution is taken out, and is added dropwise to 0.4 parts of an emulsifier at a rate of 1 drop / s under stirring at 70 to 80° C. and 200 rpm, 0.05 to 0.09 parts of sodium bicarbonate are added, and the mixture is reacted for 20 to 40 minutes, and then the remaining 2 / 3 of the mixed solution and 0.6 parts of an emulsifier are added at a rate of 3 drops / s, and the mixture is stirred at 300 rpm for 2 to 4 hours, and naturally cooled to room temperature, and the pH value is adjusted to 6 to 7 with a sodium carbonate aqueous solution to obtain a modified polyacrylic acid emulsion;

[0010] (2) 7 to 15 parts of montmorillonite and 16 to 24 parts of modified polyacrylic acid emulsion are stirred at 60 to 90° C. and 800 rpm for 12 to 18 hours, 8 to 18 parts of hydrolyzed vinyl triethoxysilane and 1 to 3 parts of ammonium persulfate are added, stirring is continued for 10 to 16 hours, and the pH value of the solution is adjusted to 6 to 8 with 10 wt % ammonia water to obtain a composite modified polyacrylic acid emulsion;

[0011] (3) 8 to 14 parts of a composite modified polyacrylic acid emulsion, 45 to 55 parts of vinyl acetate, 0.5 to 1.5 parts of ammonium persulfate, 0.1 to 0.3 parts of a preservative, 2 to 6 parts of a film-forming aid, and 44 to 62 parts of deionized water are stirred at 80 to 90° C. and 300 rpm for 3 to 7 hours, and naturally cooled to room temperature to obtain a waterproof and oil-proof high-viscosity adhesive.

[0012] Furthermore, the preparation step of the emulsifier in step (1) is as follows: 54 to 76 parts of deionized water, 1.5 to 2.1 parts of sodium dodecyl sulfate, 0.8 to 1.4 parts of octylphenyl polyoxyethylene ether, and 0.1 to 0.3 parts of ammonium persulfate are mixed at 300 rpm for 10 to 20 minutes to prepare the emulsifier.

[0013] Furthermore, the content of sodium carbonate in the sodium carbonate aqueous solution in step (1) is 5 wt %.

[0014] Furthermore, the preparation steps of the hydrolyzed vinyltriethoxysilane in step (2) are as follows: 1 to 5 parts of vinyltriethoxysilane and 6 to 40 parts of ethanol are uniformly mixed, the pH value of the solution is adjusted to 3 to 4 with aqueous hydrochloric acid solution, 3 to 25 parts of deionized water are added, and the mixture is stirred at 30 to 50° C. and 100 rpm for 0.5 to 2.5 h, cooled naturally to room temperature, and the pH value is adjusted to 7 to 8 with 10 wt % aqueous ammonia to obtain hydrolyzed vinyltriethoxysilane.

[0015] Furthermore, the concentration of hydrochloric acid in the hydrochloric acid aqueous solution is 1 mol / L.

[0016] Furthermore, the preservative in step (3) is a mixture of any one or more of sodium benzoate, methylisothiazolinone, and potassium sorbate.

[0017] Furthermore, the film-forming aid in step (3) is a mixture of any one or more of dibutyl phthalate, dioctyl adipate, and ethylene glycol.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The present invention performs cation exchange between the modified polyacrylic acid emulsion and the montmorillonite interlayer, so that the organic groups cover the montmorillonite surface or insert between the interlayers, increase the interlayer distance, improve the dispersibility and stability of the montmorillonite, enable the montmorillonite to form physical crosslinking points in the adhesive, participate in the construction of the three-dimensional network structure between the modified polyacrylic acid and polyvinyl acetate polymer molecules together with vinyl triethoxysilane, enhance the cohesive force and tensile strength of the adhesive, absorb moisture in the adhesive, form a gel structure, and increase the viscosity of the adhesive. At the same time, the introduction of Si-O-Si bonds in the adhesive can further improve the waterproof and oil-proof performance and strength of the adhesive.

[0020] Among them, the modified polyacrylic acid emulsion is prepared by copolymerizing N-hexyl-N-methacryloyloxy-N,N-dimethylaminoammonium bromide, (1-allyl-1H-benzimidazol-2-yl)methanol and acrylic acid through an emulsion method; by introducing longer chain segments, their larger spatial volume produces a steric hindrance effect, making it difficult for water molecules to break through the carbon chain barrier of long-chain alkanes, and thus being repelled from the surface of the material, thereby enhancing the waterproof and oil-proof properties of the adhesive; the benzimidazole in (1-allyl-1H-benzimidazol-2-yl)methanol can form a protective film on the bonding surface to prevent contact with media such as oxygen and moisture, thereby achieving waterproof and oil-proof effects. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the waterproof and oil-proof high-viscosity adhesive prepared in the following examples are as follows:

[0023] Bond strength: Take two wooden pieces of the same specifications, apply adhesive at 100g per square meter on the corresponding contact surface of each wooden piece. The specifications of each contact surface are 90mm*5mm. Then overlap and press the contact surfaces of the two wooden pieces correspondingly. Apply a pressure of 1Mpa on the contact surfaces. After leaving them at room temperature for 24 hours, conduct a tensile shear test.

[0024] Water resistance: Take two wooden pieces of the same specifications, apply adhesive on the corresponding contact surface of each wooden piece at a rate of 100g per square meter. The specifications of each contact surface are 90mm*5mm. Then, overlap and press the contact surfaces of the two wooden pieces correspondingly. Apply a pressure of 1Mpa on the contact surfaces. After leaving them at room temperature for 24 hours, immerse them in 60℃ water and measure the debonding time.

[0025] Viscosity: The same mass of the embodiment and the comparative example were tested according to GB / T 2794-1995.

[0026] Example 1

[0027] (1) 54 parts of deionized water, 1.5 parts of sodium lauryl sulfate, 0.8 parts of octylphenyl polyoxyethylene ether, and 0.1 parts of ammonium persulfate were mixed at 300 rpm for 10 minutes to prepare an emulsifier;

[0028] (2) 2 parts of N-hexyl-N-methacryloyloxy-N,N-dimethylaminoammonium bromide, 5 parts of (1-allyl-1H-benzimidazol-2-yl) methanol and 24 parts of acrylic acid were mixed uniformly to obtain a mixed solution, 1 / 3 of the mixed solution was taken out, and added dropwise to 0.4 parts of an emulsifier at a rate of 1 drop / s under stirring at 70° C. and 200 rpm, 0.05 parts of sodium bicarbonate were added, and the mixture was reacted for 20 minutes, and then the remaining 2 / 3 of the mixed solution and 0.6 parts of an emulsifier were added at a rate of 3 drops / s, and the mixture was stirred at 300 rpm for 2 hours, and naturally cooled to room temperature, and the pH value was adjusted to 6 with a sodium carbonate aqueous solution having a sodium carbonate content of 5 wt%, to obtain a modified polyacrylic acid emulsion;

[0029] (3) 1 part of vinyl triethoxysilane and 6 parts of ethanol were mixed uniformly, the pH value of the solution was adjusted to 3 with a 1 mol / L hydrochloric acid aqueous solution, 3 parts of deionized water were added, and the mixture was stirred at 30° C. and 100 rpm for 0.5 h, cooled naturally to room temperature, and the pH value was adjusted to 7 with 10 wt % ammonia water to obtain hydrolyzed vinyl triethoxysilane;

[0030] (4) 7 parts of montmorillonite and 16 parts of modified polyacrylic acid emulsion were stirred at 60° C. and 800 rpm for 12 h, 8 parts of hydrolyzed vinyl triethoxysilane and 1 part of ammonium persulfate were added, and stirring was continued for 10 h. The pH value of the solution was adjusted to 6 with 10 wt % ammonia water to obtain a composite modified polyacrylic acid emulsion;

[0031] (5) 8 parts of composite modified polyacrylic acid emulsion, 45 parts of vinyl acetate, 0.5 parts of ammonium persulfate, 0.1 parts of sodium benzoate, 2 parts of dibutyl phthalate, and 44 parts of deionized water were stirred at 80° C. and 300 rpm for 3 h, and naturally cooled to room temperature to obtain a waterproof and oil-proof high-viscosity adhesive.

[0032] Example 2

[0033] (1) 65 parts of deionized water, 1.8 parts of sodium lauryl sulfate, 1.1 parts of octylphenyl polyoxyethylene ether, and 0.2 parts of ammonium persulfate were mixed at 300 rpm for 15 minutes to prepare an emulsifier;

[0034] (2) 4 parts of N-hexyl-N-methacryloyloxy-N,N-dimethylaminoammonium bromide, 7 parts of (1-allyl-1H-benzimidazol-2-yl) methanol and 37 parts of acrylic acid were mixed uniformly to obtain a mixed solution, 1 / 3 of the mixed solution was taken out, and added dropwise to 0.4 parts of an emulsifier at a rate of 1 drop / s under stirring at 75° C. and 200 rpm, 0.07 parts of sodium bicarbonate were added, and the mixture was reacted for 30 minutes, and then the remaining 2 / 3 of the mixed solution and 0.6 parts of an emulsifier were added at a rate of 3 drops / s, and the mixture was stirred at 300 rpm for 3 hours, and naturally cooled to room temperature, and the pH value was adjusted to 6.5 with a sodium carbonate aqueous solution having a sodium carbonate content of 5 wt% to obtain a modified polyacrylic acid emulsion;

[0035] (3) 3 parts of vinyl triethoxysilane and 23 parts of ethanol were mixed uniformly, the pH value of the solution was adjusted to 3.5 with a 1 mol / L hydrochloric acid aqueous solution, 14 parts of deionized water were added, and the mixture was stirred at 40° C. and 100 rpm for 1.5 h, cooled naturally to room temperature, and the pH value was adjusted to 7.5 with 10 wt % ammonia water to obtain hydrolyzed vinyl triethoxysilane;

[0036] (4) 11 parts of montmorillonite and 20 parts of modified polyacrylic acid emulsion were stirred at 75° C. and 800 rpm for 15 h, 13 parts of hydrolyzed vinyl triethoxysilane and 2 parts of ammonium persulfate were added, and stirring was continued for 13 h. The pH value of the solution was adjusted to 7 with 10 wt % ammonia water to obtain a composite modified polyacrylic acid emulsion;

[0037] (5) 11 parts of composite modified polyacrylic acid emulsion, 50 parts of vinyl acetate, 1.0 part of ammonium persulfate, 0.2 parts of methylisothiazolinone, 4 parts of dioctyl adipate, and 53 parts of deionized water were stirred at 85° C. and 300 rpm for 5 h, and naturally cooled to room temperature to obtain a waterproof and oil-proof high-viscosity adhesive.

[0038] Example 3

[0039] (1) 76 parts of deionized water, 2.1 parts of sodium lauryl sulfate, 1.4 parts of octylphenyl polyoxyethylene ether, and 0.3 parts of ammonium persulfate were mixed at 300 rpm for 20 minutes to prepare an emulsifier;

[0040] (2) 6 parts of N-hexyl-N-methacryloyloxy-N,N-dimethylaminoammonium bromide, 9 parts of (1-allyl-1H-benzimidazol-2-yl) methanol and 50 parts of acrylic acid were mixed uniformly to obtain a mixed solution, 1 / 3 of the mixed solution was taken out, and added dropwise to 0.4 parts of an emulsifier at a rate of 1 drop / s under stirring at 80° C. and 200 rpm, 0.09 parts of sodium bicarbonate were added, and the reaction was carried out for 40 minutes, and then the remaining 2 / 3 of the mixed solution and 0.6 parts of an emulsifier were added at a rate of 3 drops / s, and the mixture was stirred at 300 rpm for 4 hours, cooled naturally to room temperature, and the pH value was adjusted to 7 with a sodium carbonate aqueous solution having a sodium carbonate content of 5 wt%, to obtain a modified polyacrylic acid emulsion;

[0041] (3) 5 parts of vinyl triethoxysilane and 40 parts of ethanol were mixed uniformly, the pH value of the solution was adjusted to 4 with a 1 mol / L hydrochloric acid aqueous solution, 25 parts of deionized water were added, and the mixture was stirred at 50° C. and 100 rpm for 2.5 h, cooled naturally to room temperature, and the pH value was adjusted to 8 with 10 wt % ammonia water to obtain hydrolyzed vinyl triethoxysilane;

[0042] (4) 15 parts of montmorillonite and 24 parts of modified polyacrylic acid emulsion were stirred at 90° C. and 800 rpm for 18 h, 18 parts of hydrolyzed vinyl triethoxysilane and 3 parts of ammonium persulfate were added, and stirring was continued for 16 h. The pH value of the solution was adjusted to 8 with 10 wt % ammonia water to obtain a composite modified polyacrylic acid emulsion;

[0043] (5) 14 parts of composite modified polyacrylic acid emulsion, 55 parts of vinyl acetate, 1.5 parts of ammonium persulfate, 0.3 parts of potassium sorbate, 6 parts of ethylene glycol, and 62 parts of deionized water were stirred at 90° C. and 300 rpm for 7 h, and naturally cooled to room temperature to obtain a waterproof and oil-proof high-viscosity adhesive.

[0044] Comparative Example 1

[0045] The difference between Comparative Example 1 and Example 2 is that step (4) is different. Step (4) is changed to: 20 parts of modified polyacrylic acid emulsion, 13 parts of hydrolyzed vinyl triethoxysilane, and 2 parts of ammonium persulfate are stirred at 75° C. and 800 rpm for 13 hours, and the pH value of the solution is adjusted to 7 with 10 wt % ammonia water to obtain a composite modified polyacrylic acid emulsion. The remaining steps are the same as in Example 2.

[0046] Comparative Example 2

[0047] The difference between Comparative Example 2 and Example 2 is that step (4) is different. Step (4) is changed to: 11 parts of montmorillonite and 20 parts of modified polyacrylic acid emulsion are stirred at 75° C. and 800 rpm for 15 hours, and the pH value of the solution is adjusted to 7 with 10 wt % ammonia water to obtain a composite modified polyacrylic acid emulsion. The remaining steps are the same as in Example 2.

[0048] Comparative Example 3

[0049] The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: 7 parts of (1-allyl-1H-benzimidazol-2-yl) methanol and 37 parts of acrylic acid are mixed uniformly to obtain a mixed solution, 1 / 3 of the mixed solution is taken out, and added dropwise to 0.4 parts of emulsifier at a rate of 1 drop / s under stirring at 75° C. and 200 rpm, 0.07 parts of sodium bicarbonate are added, and the reaction is carried out for 30 minutes, and then the remaining 2 / 3 of the mixed solution and 0.6 parts of emulsifier are added at a rate of 3 drops / s, stirred at 300 rpm for 3 hours, cooled naturally to room temperature, and the pH value is adjusted to 6.5 with a sodium carbonate aqueous solution having a sodium carbonate content of 5wt%, to obtain a modified polyacrylic acid emulsion. The remaining steps are the same as those of Example 2.

[0050] Comparative Example 4

[0051] The difference between Comparative Example 4 and Example 2 is that step (2) is different. Step (2) is changed to: 4 parts of N-hexyl-N-methacryloyloxy-N,N-dimethylamino ammonium bromide and 37 parts of acrylic acid are mixed uniformly to obtain a mixed solution, 1 / 3 of the mixed solution is taken out, and added dropwise to 0.4 parts of emulsifier at a rate of 1 drop / s under stirring at 75°C and 200 rpm, 0.07 parts of sodium bicarbonate are added, and the reaction is carried out for 30 minutes, and then the remaining 2 / 3 of the mixed solution and 0.6 parts of emulsifier are added at a rate of 3 drops / s, stirred at 300 rpm for 3 hours, cooled naturally to room temperature, and the pH value is adjusted to 6.5 with a sodium carbonate aqueous solution with a sodium carbonate content of 5wt%, to obtain a modified polyacrylic acid emulsion. The remaining steps are the same as those of Example 2.

[0052] Effect example

[0053] Table 1 below shows the performance analysis results of the waterproof and oil-proof high-viscosity adhesives of Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.

[0054] Table 1

[0055]

[0056]

[0057] From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Examples 1 and 2, it can be found that by performing cation exchange between the modified polyacrylic acid emulsion and the montmorillonite interlayer, the organic groups are covered on the montmorillonite surface or inserted between the interlayers, the interlayer spacing is increased, the dispersibility and stability of the montmorillonite are improved, and the montmorillonite can form physical crosslinking points in the adhesive, and participate in the construction of a three-dimensional network structure between the modified polyacrylic acid and polyvinyl acetate polymer molecules together with vinyl triethoxysilane, thereby enhancing the cohesive force and tensile strength of the adhesive, and absorbing the moisture in the adhesive to form a gel structure, thereby increasing the viscosity of the adhesive. At the same time, the introduction of Si-O-Si bonds in the adhesive can further improve the waterproof and waterproof properties of the adhesive. Oil resistance and strength; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 3, it can be found that by introducing a longer chain segment through N-hexyl-N-methacryloyloxy-N,N-dimethylaminoammonium bromide, its larger spatial volume produces a steric hindrance effect, making it difficult for water molecules to break through the carbon chain barrier of long-chain alkanes, thereby being repelled from the surface of the material, thereby enhancing the waterproof and oil-proof properties of the adhesive; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 4, it can be found that by utilizing the benzimidazole group in (1-allyl-1H-benzimidazole-2-yl)methanol, a protective film can be formed on the bonding surface to prevent contact with media such as oxygen and moisture, thereby achieving waterproof and oil-proof effects.

[0058] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A waterproof and oil-proof high-viscosity adhesive, characterized in that: The waterproof and oil-proof high-viscosity adhesive comprises, by weight, 8 to 14 parts of a composite modified polyacrylic acid emulsion, 45 to 55 parts of vinyl acetate, 0.5 to 1.5 parts of ammonium persulfate, 0.1 to 0.3 parts of a preservative, 2 to 6 parts of a film-forming aid, and 44 to 62 parts of deionized water.

2. The waterproof and oil-proof high-viscosity adhesive according to claim 1, characterized in that: The composite modified polyacrylic acid emulsion is prepared by combining modified polyacrylic acid emulsion with montmorillonite and vinyl triethoxysilane.

3. The waterproof and oil-proof high-viscosity adhesive according to claim 2, characterized in that: The modified polyacrylic acid emulsion is prepared by copolymerizing N-hexyl-N-methacryloyloxy-N,N-dimethylaminoammonium bromide, (1-allyl-1H-benzimidazole-2-yl)methanol and acrylic acid through an emulsion method.

4. A method for preparing a waterproof and oil-proof high-viscosity adhesive, characterized in that: The method comprises the following preparation steps: (1) 2 to 6 parts of N-hexyl-N-methacryloyloxy-N,N-dimethylaminoammonium bromide, 5 to 9 parts of (1-allyl-1H-benzimidazol-2-yl) methanol, and 24 to 50 parts of acrylic acid are uniformly mixed to obtain a mixed solution, 1 / 3 of the mixed solution is taken out, and is added dropwise to 0.4 parts of an emulsifier at a rate of 1 drop / s under stirring at 70 to 80° C. and 200 rpm, 0.05 to 0.09 parts of sodium bicarbonate are added, and the mixture is reacted for 20 to 40 minutes, and then the remaining 2 / 3 of the mixed solution and 0.6 parts of an emulsifier are added at a rate of 3 drops / s, and the mixture is stirred at 300 rpm for 2 to 4 hours, and naturally cooled to room temperature, and the pH value is adjusted to 6 to 7 with a sodium carbonate aqueous solution to obtain a modified polyacrylic acid emulsion; (2) 7 to 15 parts of montmorillonite and 16 to 24 parts of modified polyacrylic acid emulsion are stirred at 60 to 90° C. and 800 rpm for 12 to 18 hours, 8 to 18 parts of hydrolyzed vinyl triethoxysilane and 1 to 3 parts of ammonium persulfate are added, stirring is continued for 10 to 16 hours, and the pH value of the solution is adjusted to 6 to 8 with 10 wt % ammonia water to obtain a composite modified polyacrylic acid emulsion; (3) 8 to 14 parts of a composite modified polyacrylic acid emulsion, 45 to 55 parts of vinyl acetate, 0.5 to 1.5 parts of ammonium persulfate, 0.1 to 0.3 parts of a preservative, 2 to 6 parts of a film-forming aid, and 44 to 62 parts of deionized water are stirred at 80 to 90° C. and 300 rpm for 3 to 7 hours, and naturally cooled to room temperature to obtain a waterproof and oil-proof high-viscosity adhesive.

5. The method for preparing a waterproof and oil-proof high-viscosity adhesive according to claim 4, characterized in that: The preparation step of the emulsifier in step (1) is as follows: 54 to 76 parts of deionized water, 1.5 to 2.1 parts of sodium lauryl sulfate, 0.8 to 1.4 parts of octylphenyl polyoxyethylene ether, and 0.1 to 0.3 parts of ammonium persulfate are mixed at 300 rpm for 10 to 20 minutes to prepare the emulsifier.

6. The method for preparing a waterproof and oil-proof high-viscosity adhesive according to claim 4, characterized in that: The content of sodium carbonate in the sodium carbonate aqueous solution in step (1) is 5wt%.

7. The method for preparing a waterproof and oil-proof high-viscosity adhesive according to claim 4, characterized in that: The preparation steps of the hydrolyzed vinyl triethoxysilane in step (2) are as follows: 1 to 5 parts of vinyl triethoxysilane and 6 to 40 parts of ethanol are uniformly mixed, the pH value of the solution is adjusted to 3 to 4 with a hydrochloric acid aqueous solution, 3 to 25 parts of deionized water are added, and the mixture is stirred at 30 to 50° C. and 100 rpm for 0.5 to 2.5 h, cooled naturally to room temperature, and the pH value is adjusted to 7 to 8 with 10 wt % ammonia water to obtain hydrolyzed vinyl triethoxysilane.

8. The method for preparing a waterproof and oil-proof high-viscosity adhesive according to claim 7, characterized in that: The concentration of hydrochloric acid in the hydrochloric acid aqueous solution is 1 mol / L.

9. The method for preparing a waterproof and oil-proof high-viscosity adhesive according to claim 4, characterized in that: The preservative in step (3) is a mixture of any one or more of sodium benzoate, methylisothiazolinone and potassium sorbate.

10. The method for preparing a waterproof and oil-proof high-viscosity adhesive according to claim 4, characterized in that: The film-forming aid in step (3) is a mixture of any one or more of dibutyl phthalate, dioctyl adipate, and ethylene glycol.

Citation Information

Patent Citations

  • Single-component polyvinylacetate binding agent and preparation method thereof

    CN101906278A

  • Preparation method of medical water-based composite emulsion paper-plastic laminating adhesive

    CN110093126A

  • Organosilicon-modified acrylic emulsion adhesive and preparation method thereof

    CN110790875A